Asymmetric power in global food system advocacy - Harris, Jody (International Food Policy Research Institute, 2023)
Food systems policy has multiple legitimate aims, and different policy actors hold different values, beliefs, and interests around these issues. In low-income countries, global narratives and non-national coalitions regularly intervene in food policy processes, and they exert influence due to historical and current power relations. There are significant questions, however, about the implications and legitimacy of this international intervention into national food policies. Focusing on Zambia, this chapter finds that internationally formulated ideas are increasingly evident over time in food policy, transferred to national policy through the normative promotion of certain ways of understanding the issue of malnutrition. With its focus on multi-sectoral action to reduce stunting, the recent nutrition policy narrative impinges directly on an existing food security narrative by attempting to alter agriculture policy away from maize reliance. The nutrition policy sub-system in Zambia is therefore split, with implications for both sides on progressing a coherent policy agenda.